Indian nurses’ Knowledge, Attitude and Practice towards use of physical restraints in psychiatric patients - Gandhi, Sailaxmi; Poreddi, Vijayalakshmi; Nagarajaiah, -; Palaniappan, Marimutthu; Nikhil Reddy, S. Sai; BadaMath, Suresh (Investigación y Educación en Enfermería, 2018)
Objective. To assess nurses’ knowledge, attitude and practice towards using physical restraints among psychiatric patients. Methods. A descriptive cross sectional survey was carried out among conveniently selected sample of nurses working in psychiatry departments at a tertiary care center. The data was collected using self reported questionnaires of Suen. Results. The findings revealed that nurses had good knowledge (7.2±1.7, maximum posible=11), favorable attitudes 30.8± 3.3 (maximum posible=48) and good practice 31.2±6.2 (maximun posible=42) about use of physical restraints in psychiatric patients. Females had better knowledge (p<0.001), attitudes (p<0.05) than males towards use of physical restraints. Nurses those had more than ten years of experience found to have more favorable attitudes towards using physical restraints than nurses with less experience (p<0.05) and nurses with higher education Indian nurses’ Knowledge, Attitude and Practice towards use of physical restraints in psychiatric patients differed significantly on practice score than nurses with basic education in nursing (p<0.05). Conclusion. This study revealed good knowledge, positive attitudes and good practices among nurses about using physical restraints in mental health services. However there is need to improve even more nurses practice through continuing education programs on this topic. How to cite this article: Gandhi S, Vijayalakshmi P, Nagarajaiah, Marimuthu P, Reddy SSN, Suresh BM. Indian nurses' Knowledge, Attitude and Practice towards use of physical restraints in psychiatric patients. Invest. Educ. Enferm. 2018; 36(1):e10.